Changes in lipid profile and SOX-2 expression in RM-1 cells after co-culture with preimplantation embryos or with deproteinated blastocyst extracts. (4th May 2022) - Morato, Nicolás M.; Hallett, Judy E.; Wang, Wen-Hung; Elzey, Bennett D.; Cresswell, Gregory M.; Cooper, Bruce R.; Ferreira, Christina R.
Abstract : Mouse prostate cancer cells (RM-1) metabolically interacted with pre-implantation embryos over three days of co-culture. This interaction impacted RM-1 cells SOX-2 gene expression and lipid profile. Abstract : The embryonic environment can modify cancer cell metabolism, and it is reported to induce the loss of tumorigenic properties and even affect the differentiation of cancer cells into normal tissues. The cellular mechanisms related to this remarkable phenomenon, which is likely mediated by cell-to-cell communication, have been previously investigated with particular focus on the proteins and genes involved. In this study we report the optimization and results of a straightforward in vitro system where mouse prostate carcinoma (RM-1) cells were co-cultured for three days with preimplantation mouse embryos or spiked with deproteinated extracts from mouse blastocysts. Compared to controls, both treatments induced RM-1 cells to increase the expression of the SOX-2 gene, which is related to cellular stemness, as well as altered their lipid composition. Specific acyl-carnitines, diacylglycerols, phosphatidylglycerols, phosphatidylinositols, phosphatidylserines and cardiolipins selected using an elastic net model discriminated the treated RM-1 cells from controls. Note that the tumorigenic properties of the treated RM-1 cells were not evaluated in this research. Due to the nature of the lipids impacted in the treated RM-1 cells, we hypothesize that mitochondrial metabolism has been altered, and that small molecules both secreted from and present within the embryos might be involved in the induction of metabolic changes observed in the RM-1 cells. These molecules, which could influence cancer cell metabolism, may still be unknown ( i.e. structure, role).